Correction to: Predictors of abatacept retention over 2 years in patients with rheumatoid arthritis: results from the real-world ACTION study (Clinical Rheumatology, (2019), 38, 5, (1413-1424), 10.1007/s10067-019-04449-w) - Alten, Rieke; Mariette, Xavier; Lorenz, Hanns Martin; Nüsslein, Hubert; Galeazzi, Mauro; Navarro, Federico; Chartier, Melanie; Heitzmann, Julia; Poncet, Coralie; Rauch, Christiane; Le Bars, Manuela (Clinical Rheumatology, 2019)
The article listed above was initially published with incorrect copyright information. Upon publication of this Correction, the copyright of this article changed to “The Author(s)”. The original article has been corrected. Publisher’s note Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations.
CRIS-Team Scopus Importer:2019-05-28